2018
DOI: 10.1589/jpts.30.1176
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the Gait Deviation Index and skeletal muscle mass in children with spastic cerebral palsy

Abstract: [Purpose] This study aimed to identify a simple and useful muscle parameter for use with the Gait Deviation Index in assessment of ambulatory children with unilateral and bilateral spastic cerebral palsy. [Participants and Methods] Twenty-eight patients (aged 6 to 18 years; 16 females and 12 males) participated in this cross-sectional study. Outcome measurements included the Gait Deviation Index, grip strength, 5-repetition chair stand test, upper limb skeletal muscle mass index, and lower limb skeletal muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
5
1
1
Order By: Relevance
“…While objective gait analysis has not directly been correlated with muscle mass increase in dogs, the authors' assumption was that increased limb function would indicate a normal recovery and in turn this should be associated with continued increase in thigh muscle mass. 32 We found no relationship between changes in GRF and US; however, this may be related to the small sample size.…”
Section: Discussioncontrasting
confidence: 59%
“…While objective gait analysis has not directly been correlated with muscle mass increase in dogs, the authors' assumption was that increased limb function would indicate a normal recovery and in turn this should be associated with continued increase in thigh muscle mass. 32 We found no relationship between changes in GRF and US; however, this may be related to the small sample size.…”
Section: Discussioncontrasting
confidence: 59%
“…This condition can also be called as sarcopenia, and the ideal SMI is ranged from 5.67 to 7.23. Actually, this condition is usually reflected on the ageing population, however concerning the participants of the current study is students with physical disabilities that, functional impairment and physical disability tended to show a significant association with low skeletal muscle mass (27,28). Nevertheless, it is worth noting that some of the participants were using wheelchairs so they were not able to stand on the TANITA, body composition analyses reports were not possible to generate, thus leading to the missing values in weight and BMI.…”
Section: Body Compositionmentioning
confidence: 64%
“…In addition to that, most of the physical performance-related research only showed the improvement of disabled elderlies' flexibility in stretching and balancing exercises, like yoga and vibration exercise, as well as in resistance training (40)(41)(42). Despite having mentioned that both elderly and physically disabled have a relatively weak skeletal muscle mass compared to others, in which may have similar physical movement limitations (27,28), the current research discovered that aerobic exercises could improve the flexibility of physical disabilities.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The length of the gastrocnemius muscle during gait in normal humans is associated with the kinematics of ankle and knee joints, while the length of the soleus muscle is closely associated with the kinematics of the ankle joint (Matsunaga et al, 2018). Spasticity and contracture of muscles due to cerebral lesions can affect structural changes in the bone.…”
Section: Discussionmentioning
confidence: 99%